Editorial Pointers. (Communications of the ACM, 2006)
The article presents a letter from the editor of "Communications of the ACM" concerning the October 2006 issue. The issue focuses on the impact of globalization on computer software developers, who are cutting costs and upping productivity through globally distributed software development (GSD). While GSD lowers development costs, it makes quality control extremely difficult. The issue presents a virtual panel debate on the subject with opinions from David Parnas, Barry Boehm, Giancarlo Succi, and Matthew Simons.